The effectiveness of the peer education strategy in developing writing skills for students with learning disabilities - Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2025)
The primary aim of this study was to assess the efficacy of the peer education technique in enhancing writing skills of children who have learning disabilities. The study included a cohort of kids with learning disabilities who attended schools in the Abha Governorate. The original objective was for the experiment to have a length of 30 days. The study had a cohort of 40 students, with 20 students being allocated randomly to the experimental group and the remaining 20 students assigned to the control group. After the intervention was put into action, the experimental group showed a superior level of writing skills on assessments that measured both linguistic and content abilities, in comparison to the control group. There were no notable disparities observed in the writing proficiency scores of the experimental group, both at the follow-up assessment and immediately after the intervention.